Neuromuscular blocking agents induced anaphylaxis: Results and trends of a French pharmacovigilance survey from 2000 to 2012. Issue 11 (15th October 2018) - Petitpain, N.; Argoullon, L.; Masmoudi, K.; Fedrizzi, S.; Cottin, J.; Latarche, C.; Mertes, P. M.; Gillet, P.
Abstract: Background: Perioperative anaphylaxis mainly involves neuromuscular blocking agents (NMBAs) with an IgE‐mediated mechanism. In France, this life‐threatening condition is reported by anesthetists and allergologists, and two safety alerts concerning suxamethonium were raised in 2011 and 2012. This led to start a national survey over the 2000‐2012 period which objectives were to provide a descriptive analysis, to estimate incidence rates, and to analyze the trends over this period. Methods: The French pharmacovigilance database was retrospectively queried for all the available NMBAs. Anaphylaxis cases with elevated tryptase and positive skin tests were qualified as "confirmed cases." Subgroup analysis compared atracurium and cisatracurium vs suxamethonium and rocuronium. Results: A total of 680 confirmed cases and 944 nonconfirmed cases were identified. Suxamethonium was the most implied NMBA (64%). Incidence rates (according to sales data) of suxamethonium and rocuronium were, respectively, 10‐ and 13‐folds higher than those of the others NMBAs, regardless the confirmed/nonconfirmed status. Cisatracurium incidence rates remained stable over the period, while suxamethonium and atracurium increased and rocuronium first decreased but re‐increased after 2006. Male patients were more frequent in the subgroup "atracurium‐cisatracurium" ( P  = .019), whereas obesity and emergency setting were more frequent in the subgroup "rocuronium‐suxamethonium." Shared characteristics were the poorly documented previous exposure to NMBA(s) and an insufficient adherence of patients to perform skin tests, showing the need to improve this procedure. Conclusion: Suxamethonium and rocuronium are markedly more involved in perioperative anaphylaxis than the other available NMBAs. Patients should be more informed about their perioperative anaphylaxis and its consequences. Abstract : Perioperative anaphylaxis mainly involves neuromuscular blocking agents (NMBAs), and over the 2000‐2012 period, suxamethonium and rocuronium each had anaphylaxis incidence rates more than tenfold higher than atracurium and cisatracurium. Over this 13‐year period, the incidence rate of NMBA anaphylaxis showed a significant increase for suxamethonium and atracurium, whereas it remained stable for cisatracurium. Rocuronium displayed a 2‐period curve with a significant increase from 2005. Patients need to be more aware about the importance of allergological skin tests for ensuring safe further anesthetic procedures.